Re-evaluating US foreign policy towards Asia - Rajan, D. S.; Vasan, R. S. (R. Seshadri); Bonofer, Jacob Ashik (Chennai Centre for China Studies Centre for Asia Studies KW Publishers, 2013)
The book marks the publication of the edited volume of the proceedings of a National Seminar on 'Re-Evaluating US Foreign Policy towards Asia', organised jointly by the Chennai Centre for China Studies (C3S),Center for Asia Studies(CAS), and the University of Madras (Department of Politics and Public Administration) at Chennai on January 09, 2012